Maximizing the quality of education by measuring the educational added value in secondary school technical type on the basis of exam results = Maksymalizacja jakości kształcenia poprzez pomiar edukacyjnej wartości dodanej w szkole ponadgimnazjalnej typu technikum na podstawie wyników egzaminacyjnych - Polcyn, Jan; Czyżewski, Bazyli (Zielona Góra: Faculty of Economics and Management Press)
The rationale for this study is the search for ways to optimize expenditures on secondary vocational education. Optimization activities should lead to the creation of high quality human capital in the society. The purpose of this study is to verify the view indicating that schools with fewer students achieve higher learning outcomes. Nine classes were selected from a group of all secondary technical schools in Poland (N = 1683).
Keywords: jakość kształcenia; liczebność szkół; edukacyjna wartość dodana; ANOVA; optymalna wielkość szkoły; quality of education; number of schools; educational added value; optimum size of the school